Hypertensive response to exercise - to treat or not to treat?. (11th May 2021) - Cunha, NPD; Rodrigues, T; Silverio Antonio, P; Couto Pereira, S; Morais, P; Alves Da Silva, P; Valente Silva, B; Brito, J; David, C; Pinto, FJ; Almeida, AG
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Hypertensive response to exercise (HRE) is often documented in individuals without known cardiovascular disease. However, its impact on patient prognosis and the necessity of treatment are still not clear. Objective: We aimed to evaluate the impact of a hypertensive response (HRE) on exercise test (ET) on clinical prognosis and outcome. Methods: This was a single-center retrospective study of patients with HRE on stress exercise testing (STE) performed between January 2012 and December 2015. In our center, we define HRE as systolic blood pressure (SBP) > 210mmHg in men and >190mmHg in women, diastolic blood pressure (DBP) > 90mmHg or an increase in baseline systolic BP at least 60 mmHg in men or 50 mmHg in women, during exercise. Demographic, clinical, echocardiographic, electrocardiographic data were collected, and results were obtained using Chi-square and Student-t tests; logistic regression. Results: We evaluated 500 patients who underwent STE, 457 of which had hypertensive response vs 43 patients without HRE (mean age 57 ± 11 vs 61 ± 8 years, p = 0, 01). Among the two groups there were no differences between gender (76.5% men vs 69.7%) and race nor between the cardiovascular risk factors, namely hypertension, diabetes and dyslipidaemia. We evaluated their responses in STE and their outcomes, with a mean follow-up of 60 ± 22 months. In the univariate and multivariate analysis, presence of Sokolow-Lion criteria of left ventricular hypertrophy in the ECG was associated with HRE during the exam (OR 5.26; CI95% 2.4-11.6; p < 0.001). In patients who had previously known hypertension, therapy with calcium channel blockers seemed to protect against hypertensive response prior to ET (OR 0.48, CI95% 0.24-0.97, p = 0.004) compared to other antihypertensive drugs. Regarding the clinical outcomes, patients with HRE were associated with an increased risk of developing heart failure (p = 0.027) (versus patients without HRE) during follow up but failed to predict adverse outcomes such as acute coronary syndrome, atrial fibrillation or stroke. Within the patients with HRE in ET, 78 patients did not have an established diagnosis of HTA (mean age 49 ± 12.16 years, 75.6% men). In these patients we observed initiation on antihypertensive therapy after ET on 27.6% patients, but on univariate and multivariate analysis, starting therapy with anti-hypertensives did not have a significant impact on incidence of stroke, AF, HF, hospitalization for cardiovascular events or death. Conclusions: We did not observe any significant differences among the studied groups regarding prognosis, except for the highest incidence of heart failure in patients with HRE. Initiation of antihypertensive therapy in patients with HRE failed to modify outcomes, however our sample was underpowered, so, further studies are required in order to clarify the value of treatment in patients with HRE.